Molecular turnover, the H3.3 dilemma and organismal aging (hypothesis). Issue 3 (26th February 2015) - Saade, Evelyne; Pirozhkova, Iryna; Aimbetov, Rakhan; Lipinski, Marc; Ogryzko, Vasily
Summary The H3.3 histone variant has been a subject of increasing interest in the field of chromatin studies due to its two distinguishing features. First, its incorporation into chromatin is replication independent unlike the replication‐coupled deposition of its canonical counterparts H3.1/2. Second, H3.3 has been consistently associated with an active state of chromatin. In accordance, this histone variant should be expected to be causally involved in the regulation of gene expression, or more generally, its incorporation should have downstream consequences for the structure and function of chromatin. This, however, leads to an apparent paradox: In cells that slowly replicate in the organism, H3.3 will accumulate with time, opening the way to aberrant effects on heterochromatin. Here, we review the indications that H3.3 is expected both to be incorporated in the heterochromatin of slowly replicating cells and to retain its functional downstream effects. Implications for organismal aging are discussed.